Neurofilament levels as biomarkers in asymptomatic and symptomatic familial amyotrophic lateral sclerosis. Issue 1 (17th December 2015) - Weydt, Patrick; Oeckl, Patrick; Huss, André; Müller, Kathrin; Volk, Alexander E.; Kuhle, Jens; Knehr, Antje; Andersen, Peter M.; Prudlo, Johannes; Steinacker, Petra; Weishaupt, Jochen H.; Ludolph, Albert C.; et al.
Abstract : Neurofilaments are elevated in the cerebrospinal fluid (CSF) and serum of amyotrophic lateral sclerosis (ALS) patients. However, timing of this increase is unknown. To characterize the premanifest disease phase, we performed a cross‐sectional study on asymptomatic (n = 12) and symptomatic (n = 64) ALS mutation carriers and family controls (n = 19). Neurofilaments NF‐L (neurofilament–light chain) and pNF‐H (phosphorylated neurofilament–heavy chain) are normal before symptom onset and increased by at least an order of magnitude at early symptom onset in CSF (pNF‐H) or serum and CSF (NF‐L). Thus, blood and CSF neurofilament levels are linked to the symptomatic phase of ALS and might serve as objective markers of structural damage to the nervous system. ANN NEUROL 2016;79:152–158